Reduced erythroid cell and erythropoietin production in response to acute anemia in prion protein-deficient (Prnp-/-) mice - Živný, Jan; Gelderman, Monique P; Xu, Fei; Piper, John; Holada, Karel; Šimák, Jan; Vostál, Jaroslav (Blood cells, molecules, & diseases, 2008)
Cellular prion protein (PrPc) participates in the pathogenesis of prion diseases but its normal function remains unclear. PrPc is expressed on hematopoietic cells, including erythroid precursors. We investigated the role of PrPc in erythropoiesis in vivo with phenylhydrazine-induced acute anemia. Induction of equivalent anemia in wild-type (WT) and Prnp-/- mice resulted in a higher number of circulating reticulocytes, hematocrits and spleen weights in WT mice than in Prnp-/- mice on Days 5 and 7. Examination of bone marrow erythroid precursor cells (Ter119+) on Day 5 revealed no significant differences in the number of these cells between the two types of animals. However, a higher percentage of Ter119+ cells were going through apoptosis in Prnp-/- mice than in WT mice. Plasma erythropoietin (Epo) levels and Epo mRNA in kidneys peaked on Day 3 in response to anemia for both types of animals but rose less in Prnp-/- (5500 pg/ml ) than in WT (18,000 pg/ml) animals. Administration of recombinant human Epo to mice produced an equivalent reticulocyte response in both types of animals suggesting that the potential for erythroid generation is intact in Prnp-/- animals. These observations indicate that PrPc may modulate tissue hypoxia-sensing mechanisms or effect hypoxia target gene expression.
Keywords: retikulocyty; mutantní kmeny myší; erytropoéza; Erythroid Precursor Cells; erythropoetin; Reticulocytes; fenylhydraziny; financování organizované; Phenylhydrazines; Hypoxia; oxidancia; Financing, Organized; Erythropoietin; zvířata; myši; Mice; erytroidní prekurzorové buňky; hypoxie; myši knockoutované; Erythropoiesis; PrPC proteiny; Mice, Knockout; hemolytické anemie; Anemia, Hemolytic; Oxidants; Mice, Mutant Strains; Animals; Acute Disease; akutní nemoc; PrPC Proteins